Iron oxide nanoparticles doped biochar ameliorates trace elements induced phytotoxicity in tomato by modulation of physiological and biochemical responses: Implications for human health risk. (February 2022) - Naeem, Muhammad Asif; Abdullah, Muhammad; Imran, Muhammad; Shahid, Muhammad; Abbas, Ghulam; Amjad, Muhammad; Natasha,; Shah, Ghulam Mustafa; Khan, Waqas-ud-Din; Alamri, Saud; Al-Amri, Abdullah A.
Abstract: Use of untreated municipal wastewater (WW) contains toxic trace elements that pose a serious threat to the soil-plant-human continuum. The use of biochar (BC) is a promising approach to minimize trace element induced toxicity in the ecosystem. Therefore, the present study aims to evaluate the efficacy of BC derived from wheat straw and iron oxide nanoparticles doped biochar (IO-BC) to reduce trace element buildup in soil and plants that consequently affect tomato plant growth and physiological activity under WW irrigation. The BC and IO-BC were applied at four levels (0, 0.5, 1, and 1.5%) in WW irrigated soils. The results indicated that the addition of WW + BC and WW + IO-BC resulted in significant reduction in trace element mobility in soil. Interestingly, the application of WW + IO-BC (1.5%) was more effective in reducing trace element mobility and bioavailability in soil by 78% (As), 58% (Cr), 46% (Pb) and 50% (Cd) compared to WW irrigation, and thus reduced trace element accumulation and toxicity in plants. Results revealed that WW irrigation negatively affected tomato growth, fruit yield, physiology and antioxidative response. Addition of WW + BC and WW + IO-BC ameliorated the oxidative stress (up to 65% and 58% in H2 O2 and MDA) and increased plant tolerance (up to 49% in POD and APX activity). The risk indices also showed minimum human health risk (H1 < 1) from tomato after the addition of BC or IO-BC in WW irrigated soils. It is concluded that IO-BC addition in WW irrigated soil could assist in reducing trace elements accumulation and toxicity in tomato and associated human health risks. Graphical abstract: Image 1 Highlights: Trace elements accumulation impaired growth and physiology of tomato under wastewater (WW) irrigation. Toxic ion accumulation resulted in limited uptake of essential nutrients and oxidative stress. Iron oxide nanoparticles doped biochar (IO-BC) was more effective than biochar (BC). IO-BC decreased oxidative stress by upregulating antioxidant enzymes. Human health risk was greatly decreased in the presence of IO-BC